Neonatal thrombocytopenia - Somalika Pal; Ashish Jain (Wolters Kluwer Medknow Publications, 2019)
Thrombocytopenia is a common problem in the Neonatal Intensive Care Unit (NICU). Traditionally defined at platelet counts of less than 1.5lakhs/mm3, it is a common observation that several healthy new-borns too have values below this threshold. Neonatal platelets have some unique developmental variations which allow them to maintain hemostasis and not manifest with clinical bleeding. The effects of transfusing adult platelets into a delicately and differently poised neonatal haemostatic system has been debated and has resulted in ambiguity in the prescription of ideal transfusion thresholds for thrombocytopenic neonates. This review aims at highlighting these unique developmental variations of neonatal platelets, discussing the existing definition of neonatal thrombocytopenia, understanding the fallacies of different methods of analysing platelet counts, evaluating the various causes of neonatal thrombocytopenia and the mechanisms leading to thrombocytopenia in each. Ultimately, this review is to help in the approach to a neonate with thrombocytopenia with or without clinical bleeding, understand the transfusion triggers for such newborns, know the various platelet types available for transfusion and how to transfuse them, analyse the response to such transfusion and draw reasonable conclusions pertaining to the disease afflicting such newborns.